Assessment of skin lesions produced by focused, tunable, mid‐infrared chalcogenide laser radiation. Issue 9 (25th May 2018) - Evers, Michael; Ha, Linh; Casper, Malte; Welford, David; Kositratna, Garuna; Birngruber, Reginald; Manstein, Dieter
Abstract : Background: Traditionally, fractional laser treatments are performed with focused laser sources operating at a fixed wavelength. Using a tunable laser in the mid‐infrared wavelength range, wavelength‐dependent absorption properties on the ablation process and thermal damage formation were assessed with the goal to obtain customizable tissue ablations to provide guidance in finding optimized laser exposure parameters for clinical applications. Methods: Laser tissue experiments were carried out on full thickness ex vivo human abdominal skin using a mid‐infrared tunable chromium‐doped zinc selenide/sulfide chalcogenide laser. The laser has two independent channels: a continuous wave (CW) output channel which covers a spectrum ranging from 2.4 μm to 3.0 μm with up to 9.2 W output power, and a pulsed output channel which ranges from 2.35 μm to 2.95 μm. The maximum pulse energy of the pulsed channel goes up to 2.8 mJ at 100 Hz to 1, 000 Hz repetition rate with wavelength‐dependent pulse durations of 4–7 ns. Results: Total ablation depth, ablation efficiency, and coagulation zone thickness were highly correlated to wavelength, pulse width, and pulse energy. Using the same total radiant exposure at 2.85 μm wavelength resulted in 10‐times smaller coagulation zones and 5‐times deeper ablation craters for one hundred 6 ns pulses compared to one 100 ms pulse. For a fixed pulse duration of 6 ns and a total radiant exposure of 2.25 kJ/cm 2 the ablation depth increased with longer wavelengths. Conclusion: The tunable laser system provides a useful research tool to investigate specific laser parameters such as wavelength on lesion shape, ablation depth and thermal tissue damage. It also allows for customization of the characteristics of laser lesions and therefore facilitates the selection of suitable laser parameters for optimized fractional laser treatments. Lasers Surg. Med. 50:961–972, 2018.© 2018 Wiley Periodicals, Inc.